A COMPARATIVE STUDY OF VFX-DRIVEN BOLLYWOOD FILMS AND CONTENT-DRIVEN FILMS WITH MINIMAL VFX - Kamal, Prashant; Mukherjee, Tanushri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In recent years, Bollywood has witnessed a transformative shift, with visual effects (VFX) becoming a dominant force in storytelling. This trend has sparked a debate on whether cinematic success hinges on visual spectacle or narrative depth. Understanding this dichotomy is essential for evaluating the evolving preferences of modern audiences. This research paper delves into the growing prominence of VFX-driven films in contrast to content-driven narratives with minimal VFX. It offers a comparative analysis of audience preferences for these two distinct categories of films. The study employing secondary data analysis method, drawing on existing literature revolving around the study of box office data, audience surveys, and critical reviews, examines factors influencing viewer choices, including storyline, actions, characters, special effects and other cinematics (etc). The research investigates whether audiences prioritize visual extravagance over compelling storytelling or if a balance between the two is critical for achieving critical acclaim and commercial success. The findings provide valuable insights into the shifting landscape of Bollywood cinema, highlighting the interplay between technological advancements and audience expectations. This study contributes significantly to film studies and offers a nuanced understanding of contemporary Bollywood filmmaking.